Protective Effect of a Hyperimmune Serum Against Homologous Enterococcus cecorum Infection in Experimentally Challenged Meat-Type Chickens - Amanda Rosenbaum; Silke Rautenschlein; Arne Jung (Poultry)
Knowledge about chickens’ immune response to infection with Enterococcus cecorum (EC) and prophylactic strategies is scarce. This study aimed to investigate the protective effect of an EC-specific hyperimmune serum after experimental challenge with homologous EC. A total of 284 one-day-old meat-type chickens were randomly assigned to three groups (non-inoculated (C), passively immunized with hyperimmune serum and EC-inoculated (EPI), and EC-inoculated (E)). At 1 and 2 days post-hatch (dph), the hyperimmune serum was subcutaneously administered to each chicken in group EPI. Oral inoculation with EC was carried out at 2 dph. Blood samples and cloacal swabs were collected at 7, 14, 21, 28, and 35 dph and necropsy was carried out at 42/43 dph. Extraintestinal colonization with EC was significantly decreased in group EPI compared to group E. Additionally, femoral head necrosis and spondylitis of the free thoracic vertebra were significantly decreased in group EPI compared to group E. Flow cytometric analysis revealed a significant increase in heterophils, monocytes, and the heterophil/lymphocyte ratio in the peripheral blood of bacteriological positive chickens. Although the parenteral application of a hyperimmune serum lacks practicability in meat-type chicken flocks, the results of this study encourage further research on vaccination of meat-type chicken breeder flocks.